Design Analysis Pillowblock Strength of Rotogravure Gearbox Uses Catia V5 Software - Agung Nugroho; Yudiono, Heri (Universitas Negeri Semarang, 2024)
The pillowblock has not been tested to determine the von Mises stress, displacement and safety factor values. The aim of this research is to analyze the results of the Pillowblock design analysis using the finite element method using CATIA V5 software.The research method used in this research is an experimental method. In this study, the independent variable used was variations in the thickness dimensions of the Rotogrvure Pillowblock Gearbox. The variations used are Pillowblock Close 1 with varying thicknesses (5 mm, 4 mm, 6 mm, 7 mm), Pillowblock Close 2 with varying thicknesses (6 mm, 5 mm, 7 mm, 8 mm) and Pillowblock Equipment with varying thicknesses (5 mm, 4 mm, 6 mm, 7 mm), the material used is ST 40 with a rotary bending load (bearing load). Tests were carried out using the fenite element method (FEM) to determine the value of von Mises stress, displacement and safety factor. The analysis results show that variations in pillowblock thickness have a high level of effectiveness and efficiency and have a safety factor value of ≥ 2, found in the Pillowblock Close 1 T4 (7 mm) with a von Mises stress value of 0.349 MPa, displacement 0.000046 mm, safety factor 787.96. Pillowblock Close 2 R4 (8 mm) with a von Mises stress value of 0.430 MPa, displacement 0.000062 mm, safety factor 639.24, and Pillowblock Equipment P4 (7 mm) with a von Mises stress value of 2.504 MPa, displacement 0.000312, safety factor 109.82.